Tunica dartos thermoregulatory index in bull and ram in Egypt - El-Darawany, A A (The Indian Journal of Animal Sciences, 2012)
This study was carried out on Holstein-Friesian bulls and Ossimi rams. Measurement of Tunica dartos index (TDI) was estimated by circulating the scrotum in cold and warm water bath. Significant categories of TDI differences were demonstrated in libido, wave motion, sperm motility, dead sperm %, sperm abnormalities (pyriform cells, midpiece and acrosomal abnormality), sperm concentration and acrosomal reaction in bull and ram, and serum testosterone concentration in ram only, and, conception rate and cows calving and ewes lambing. The TDI studied may have some value in reflecting the status of semen quality and reproductivity.